Combination of Foot Massage and Active Range of Motion in Nursing Care for Diabetic Neuropathy Patients with Ineffective Peripheral Perfusion: a Case Study - Halimatus Sa'diyah; Jon Hafan Sutawardana; Ruris Haristiani; Jumanto Jumanto (Jurnal Ilmiah Kesehatan Rustida, 2026)
Diabetic neuropathy is one of the most common chronic complications found in patients with type 2 diabetes mellitus, characterized by decreased foot sensitivity and impaired peripheral circulation. A frequently encountered nursing problem is ineffective peripheral perfusion, which increases the risk of diabetic foot ulcers and amputation. Non-pharmacological interventions such as foot massage and active range of motion (ROM) exercises have been proven effective in enhancing peripheral perfusion and sensory function. This study aims to explore the implementation of a combination of foot massage and active ROM exercises in improving sensitivity and peripheral circulation in patients with diabetic neuropathy. A case study design was used, employing a nursing care approach based on Evidence-Based Nursing (EBN). The therapy was administered over three consecutive days, consisting of a 25–30-minute foot massage followed by approximately 30 minutes of active ROM exercises each morning. Evaluation was conducted using the Toronto Clinical Neuropathy Score (TCNS) and Ankle Brachial Index (ABI) screening with Doppler ultrasound before and after the intervention. The results showed a decrease in TCNS score from 12 (severe neuropathy) on the first day to 6 (mild neuropathy) on the third day. ABI values increased from 0.30 (severe) to 0.71 (mild). Improvements were also observed in capillary refill time, skin color, reduced edema, and decreased paresthesia. In conclusion, the combination of foot massage and active ROM exercises effectively improved sensitivity and peripheral circulation in patients with diabetic neuropathy, thereby supporting conventional therapies provided during hospital care.